REPRESENTASI WANITA DALAM JOSEIGO - Krishna Adnyani, Kadek Eva (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2013)
The qualitative research is aimed at describing the women representation in Joseigo (women language) which occured in Japanese Language. The data of the research were the special words, including terms, accent, intonation, pronounciation, and grammar which exclusively referred to be used by Japanese Women. The findings show that the formulation of Joseigo is not something that naturally occured or indication of the ideal femininity but a part of government’s manipulation. Joseigo then constructed by media as a way to elevate thesocial status of women and as a femininity index.